Expression and function of matrix Gla protein in human peritoneal mesothelial cells - Zhai, Yihui; Chen, Ling; Hömme, Meike; Hackert, Thilo; Groß-Weissmann, Marie-Luise; Hoffmann, Georg F.; Schaefer, Franz; Schmitt, Claus P. (Nephrology, dialysis, transplantation, 2010)
Background. Chronic peritoneal dialysis (PD) is associated with peritoneal calcification. Studies in vascular tissue suggest that ectopic calcification is not merely a passive but a regulated process resembling bone mineralization. We investigated whether peritoneal calcification is controlled by matrix Gla protein (MGP) secreted by peritoneal mesothelial cells.Methods. Human primary mesothelial cells (HPMC) were exposed to constituents of PD fluids and to cytokines relevant to peritoneal integrity. Messenger RNA was quantitated by real-time reverse transcription polymerase chain reaction (RT-PCR), protein abundance by Western blot and in vivo protein expression immunohistochemically. To demonstrate functional relevance, MGP was silenced in HPMC by siRNA transfection and calcium phosphate matrix deposition measured by o-cresolphthalein complexone method and von Kossa staining.Results. MGP was consistently detected in the mesothelial cell layer of peritoneal tissue specimens from uraemic and non-uraemic patients, in HPMC and in culture medium. MGP mRNA and protein abundance was increased by glucose and IGF1 and decreased by TGFß1. Suppression of MGP increased matrix calcium and phosphorus deposition by 90 ± 6% and 100 ± 4% at 1 mM ambient Ca2+ and phosphorus concentration. Deposition was not increased any further by higher medium Ca2+/phosphorus concentrations nor reduced by inhibition of the phosphate cotransporter Pit1.Conclusion. MGP is expressed by HPMC and regulated by glucose, IGF1 and TGFß1. It is a potent inhibitor of calcification in vitro and may thus play a role in the regulation of peritoneal calcium homeostasis.